2019
DOI: 10.1186/s12866-019-1616-2
|View full text |Cite|
|
Sign up to set email alerts
|

Aging progression of human gut microbiota

Abstract: BackgroundHuman gut microbiota are important for human health and have been regarded as a “forgotten organ”, whose variation is closely linked with various factors, such as host genetics, diet, pathological conditions and external environment. The diversity of human gut microbiota has been correlated with aging, which was characterized by different abundance of bacteria in various age groups. In the literature, most of the previous studies of age-related gut microbiota changes focused on individual species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 66 publications
3
125
2
2
Order By: Relevance
“…Recent studies have yielded insight into the intricate interactions between age and the gut microbiota by 16S rRNA sequencing [ 10 ]. With increasing age, it has been observed a gradual and steady reduction in the population of aerobes and facultative anaerobes, in concert with a simultaneous upsurge in the number of anaerobes [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have yielded insight into the intricate interactions between age and the gut microbiota by 16S rRNA sequencing [ 10 ]. With increasing age, it has been observed a gradual and steady reduction in the population of aerobes and facultative anaerobes, in concert with a simultaneous upsurge in the number of anaerobes [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies exploring bacterial 16S rDNA genes have yielded insight into the intricate interactions between age and the gut microbiota (13). With increasing age, there is a gradual and steady reduction in the population of aerobes and facultative anaerobes, in concert with a simultaneous upsurge in the number of anaerobes (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, although healthy pre-adolescent children (ages 7-12 years) and adults harbored similar numbers of taxa and functional genes, their relative composition differed signi cantly (4). Nonetheless, a large scale study by Enck et al using conventional colony plating to assess numbers of several bacterial genera, found no noticeable changes in children between [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] years old, including stable levels of Bi dobacterium and Lactobacillus (5). Recently, with the expansion and availability of bacterial DNA sequencing technology, a study revealed that comparison of distal intestinal microbiota composition between adolescents (11-18 years of age) and adults, a statistically signi cant higher abundance of the genera Bi dobacterium and Clostridium was found in adolescent samples.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have yielded insight into the intricate interactions between age and the gut microbiota by 16S rDNA sequencing (13). With increasing age, it has been observed a gradual and steady reduction in the population of aerobes and facultative anaerobes, in concert with a simultaneous upsurge in the number of anaerobes (5,14).…”
Section: Discussionmentioning
confidence: 99%